Long-term clinical outcomes after percutaneous coronary intervention for chronic total occlusions - Spyretta Golemati; Elias A. Sanidas; George D. Dangas (Curr Cardiol Rep, 2014)
Optimal treatment of chronic total occlusions (CTOs) remains one of the major challenges in interventional cardiology. A number of factors, including both patient clinical conditions and technical procedural considerations, have been identified to affect percutaneous coronary intervention (PCI) success and long-term outcomes, in large multicenter cohorts as well as smaller patient groups. As opposed to patient-centered factors, technical factors can be managed and as a result, a lot of research aims at improving stent technology and imaging guidance, toward enhancing PCI efficiency, in regards to patient safety.